2020
DOI: 10.1007/s40003-020-00501-3
|View full text |Cite
|
Sign up to set email alerts
|

Association of GnRH1 Gene with Growth Traits in Two Breeds of Sheep

Abstract: The present study was conducted to identify the associations between the genetic polymorphisms of GnRH1 gene and growth traits in Awassi and Karakul breeds of sheep. Two GnRH1 amplicons of 313 bp and 323 bp were designed to cover exon 1, exon 2, and their flanking regions, respectively. Genotyping experiments were performed using PCR-SSCP and DNA sequencing. No polymorphism was observed in 323 bp amplicons, while two SSCP-banding patterns were detected in 313 bp amplicons with the presence of two genotypes (AA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…Body weights and measurements are quantitative traits that are determined through the interaction between environment and genetics, as studies have indicated the role of genes carried by the breed and the surrounding environmental conditions are responsible for the difference in the development of body weight through the influence of many genes that act differently [8,23]. The results of the current study were supported by [24], on Karakul sheep at birth and weaning weights and six months of age, and [25], when studied on Awassi sheep. While the results of our study did not agree with [26], in the Indian Marwari and Karakul breeds.…”
Section: Breed and Sex Lambssupporting
confidence: 72%
“…Body weights and measurements are quantitative traits that are determined through the interaction between environment and genetics, as studies have indicated the role of genes carried by the breed and the surrounding environmental conditions are responsible for the difference in the development of body weight through the influence of many genes that act differently [8,23]. The results of the current study were supported by [24], on Karakul sheep at birth and weaning weights and six months of age, and [25], when studied on Awassi sheep. While the results of our study did not agree with [26], in the Indian Marwari and Karakul breeds.…”
Section: Breed and Sex Lambssupporting
confidence: 72%
“…However, no significant effect of the sex of the lambs was reported on the live body weights and weight gain in the Syrian Awassi sheep (Aljubouri et al, 2020b). The difference in the live body weight measurements between males and females with the progress of age may be due to the increasing differences in the endocrine system and the role of the male hormones, which are essential for building bones and muscle growth (Karsenty & Olson, 2016).…”
Section: Association Of T4 and Gh Levels With Sexmentioning
confidence: 99%
“…However, the growth of lambs is affected by many factors, including genetic factors, the birth season, the age of dams, the sequence of birth, the sex of lambs and the weaning period (Jawasreh et al, 2019). Improving sheep's growth traits is the main concern of many researchers, and growth trait is the most important economic factor in animals, which is controlled by several genes (Aljubouri et al, 2020b;Imran et al, 2021). One of the most prevalent sheep breeds in Iraq is Awassi, with 58.2% of prevalence over other breeds, such as Arabi (21.8%) and Karadi (20%) (Aljubouri & Al-Shuhaib, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…However, the growth of lambs is influenced by many factors, including genetic factors, birth season, age of birth, sequence of birth, sex of lambs and weaning period [10]. Improving sheep growth traits is the basis of concern for many researchers, and growth traits is the most important economic factors in animals controlled by several genes [11,12].…”
Section: Introductionmentioning
confidence: 99%